IMPLEMENTASI PENERAPAN METODE SIX SIGMA PADA PROSES PERAKITAN ELEKTRO MOTOR (STUDI KASUS: PT. TATUNG ELECTRIC INDONESIA) - Arief Suardi Nur Chairat (Sekolah Tinggi Teknik - PLN, 2015)
Tatung Electric Indonesia is a peripatetic company in manufacturing industry assembling of electro motor. So that product yielded by PT. Tatung Electric Indonesia can continue to fulfill requirement of customer, company try to improve the quality of its product by minimizing defect which during the time still happened. This defect arising caused by the existence of variation at yielded product and also that happened in the process. Six Sigma represent control technique or method to reach storey or level quality of 3.4 DPMO ( Defects Per Million Opportunities), which applied by Motorola company since year 1986. Applying strategy to be used is Define-Measure-Analyze-Improve-Control (DMAIC). This Method represent recuring step and form a make-up of quality cycle. Calculations show the company is 3.641 sigma level with DPMO 15,830. The sigma levels are on the average level of sigma industries in Indonesia (3-4 sigma). Increased levels of sigma would happen if the company immediately continuous improvement over time. Conclusion of the application of Six Sigma is the DMAIC method in the assembly process of electro motors can analyze and reduce disability that occurs that will increase the quality of products.